N-3 polyunsaturated fatty acids may affect the course of COVID-19 - Lampova, Barbora; Doskocil, Ivo; Kourimska, Lenka; Kopec, Aneta (Frontiers in Immunology, 2022)
The highly infectious coronavirus disease (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is a new coronavirus that has been spreading since late 2019 and has caused millions of deaths worldwide. COVID-19 continues to spread rapidly worldwide despite high vaccination coverage; therefore, it is crucial to focus on prevention. Most patients experience only mild symptoms of COVID-19. However, in some cases, serious complications can develop mainly due to an exaggerated immune response; that is, a so-called cytokine storm, which can lead to acute respiratory distress syndrome, organ failure, or, in the worst cases, death. N-3 polyunsaturated fatty acids and their metabolites can modulate inflammatory responses, thus reducing the over-release of cytokines. It has been hypothesized that supplementation of n-3 polyunsaturated fatty acids could improve clinical outcomes in critically ill COVID-19 patients. Some clinical trials have shown that administering n-3 polyunsaturated fatty acids to critically ill patients can improve their health and shorten the duration of stay in intensive care. However, previous clinical studies have some limitations; therefore, further studies are required to confirm these findings.